3D FTO/FTO‐Nanocrystal/TiO2 Composite Inverse Opal Photoanode for Efficient Photoelectrochemical Water Splitting. Issue 20 (17th April 2018) - Wang, Zhiwei; Li, Xianglin; Ling, Han; Tan, Chiew Kei; Yeo, Loo Pin; Grimsdale, Andrew Clive; Tok, Alfred Iing Yoong
Abstract: A 3D fluorine‐doped SnO2 (FTO)/FTO‐nanocrystal (NC)/TiO2 inverse opal (IO) structure is designed and fabricated as a new "host and guest" type of composite photoanode for efficient photoelectrochemical (PEC) water splitting. In this novel photoanode design, the highly conductive and porous FTO/FTO‐NC IO acts as the "host" skeleton, which provides direct pathways for faster electron transport, while the conformally coated TiO2 layer acts as the "guest" absorber layer. The unique composite IO structure is fabricated through self‐assembly of colloidal spheres template, a hydrothermal method and atomic layer deposition (ALD). Owing to its large surface area and efficient charge collection, the FTO/FTO‐NC/TiO2 composite IO photoanode shows excellent photocatalytic properties for PEC water splitting. With optimized dimensions of the SnO2 nanocrystals and the thickness of the ALD TiO2 absorber layers, the 3D FTO/FTO‐NC/TiO2 composite IO photoanode yields a photocurrent density of 1.0 mA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE) under AM 1.5 illumination, which is four times higher than that of the FTO/TiO2 IO reference photoanode. Abstract : A 3D fluorine‐doped SnO2 (FTO)/FTO nanocrystal (NC)/TiO2 inverse opal (IO) structure is designed and fabricated as a new "host and guest" type of composite photoanode for efficient photoelectrochemical water splitting. Owing to the large surface area and efficient charge collection, the FTO/FTO‐NC/TiO2 composite IO photoanode shows improved PEC performance than the FTO/TiO2 IO reference photoanode.